ChemInform Abstract: Chiral Bicyclic NHC/Ir Complexes for Catalytic Asymmetric Transfer Hydrogenation of Ketones. Issue 7 (January 2016) - Yoshida, Kazuhiro; Kamimura, Takumi; Kuwabara, Hiroshi; Yanagisawa, Akira
Abstract: Various alkylarylketones are hydrogenated in high yields and with high enantiomeric purity.